STAFF SATISFACTION ESTIMATION SYSTEMS IN RUSSIAN NATIONAL RESEARCH UNIVERSITIES - Natalia A. Novokreshchenova (Образование и наука)
The aim of the investigation is to study practical approaches to the assessment of employee satisfaction in higher education institutions; to identify and determine the maturity level of assessment systems established in the universities.Methods. The methods involve general and special methods of scientific knowledge such as analogy, systemic and structural analysis, content analysis, and comparison method.Results. The paper presents the results of practical research on Russian universities activities on the sphere of the employee satisfaction assessment. 29 Russian national research universities were selected for the analysis. The levels of systems development of a satisfaction assessment of the personnel and approaches to such procedures are designated on the basis of the content of internal university documents. It is noted that development of satisfaction assessment systems of the personnel of high schools, complex revealing both subjective, and its objective indicators will allow the staff to make more well-founded administrative decisions, and to raise interest of employees in evolution of activity of educational institution; expenses reduction by high school of time and intellectual resources can become an economic benefit.Scientific novelty and practical significance. Material, presented in the paper, can be useful to employees of HR and quality control departments of higher educational institutions of Russia; as well as to managers who work in the education system and participate in the work of staff satisfaction evaluation. Theoretical aspects of the paper can become the basis for the formation and development of models of staff satisfaction evaluation systems and the starting point of any research related to the development of guidelines for the satisfaction staff assessment.